Board Compensation Characteristics and Firm Performance: The Empirical Evidence from Listed Firms in The Market for Alternative Investment, Thailand - ยศบุตร อรุณี (Trends of Humanities and Social Sciences Research, 2021)
The purpose of this study is to examine the relationship between board compensation characteristics and performance of firms listed on The Market for Alternative Investment, Thailand. The 144 firms listed on The Market for Alternative Investment in 2018 data are collected from annual reports, 56-1 forms, and firms’ financial statements. Using multiple regression analysis, this study finds that the independent committee compensation is positively associated to firm performance. Furthermore, firm size which is control variable in this study is positively associated to firm performance. These results imply that board compensation characteristic is associated with performance of firms listed on The Market for Alternative Investment, Thailand.